2015
DOI: 10.1021/acs.jafc.5b02860
|View full text |Cite
|
Sign up to set email alerts
|

Determinations for Pesticides on Black, Green, Oolong, and White Teas by Gas Chromatography Triple-Quadrupole Mass Spectrometry

Abstract: Black, green, white, and Oolong teas, all derived from leaves of Camellia sinensis, are widely consumed throughout the world and represent a significant part of the beverages consumed by Americans. A gas chromatography-triple quadrupole-based method, previously validated for pesticides on dried botanical dietary supplements, including green tea, was used to measure pesticides fortified into black and green teas at 10, 25, 100, and 500 μg/kg. Teas from 18 vendors of tea products were then surveyed for pesticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 27 publications
6
27
0
Order By: Relevance
“…According to the data, the proposed methodology presents recovery, LODs and LOQs in the same order of magnitude of currently sample preparation techniques, such as SPE, SPME, magnetic nanoparticles extraction (MNP), dynamic hollow fiber protected liquid phase microextraction (DHFP-LPME) and quick, easy, cheap, effective, robust and safe method (QuEChERS), even when they were combined with gas chromatography with electron capture detector (GC-ECD), two-dimensional gas chromatography (GC×GC) and tandem mass spectrometry (MS/MS) systems. 6,22,23,[26][27][28] Furthermore, the reduced costs associated, labor intensity and time effectiveness (in spite of long extraction time), are fairly better when compared with other approaches (e.g., SPE, SPME). The developed method is an alternative to current extraction methods, with comparable LOD and LOQ, and satisfactory recovery for trace analysis of α and β-endosulfan in tea and yerba mate samples.…”
Section: Validation Of the Baµe(hlb)/lvi-gc-ms(sim) Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data, the proposed methodology presents recovery, LODs and LOQs in the same order of magnitude of currently sample preparation techniques, such as SPE, SPME, magnetic nanoparticles extraction (MNP), dynamic hollow fiber protected liquid phase microextraction (DHFP-LPME) and quick, easy, cheap, effective, robust and safe method (QuEChERS), even when they were combined with gas chromatography with electron capture detector (GC-ECD), two-dimensional gas chromatography (GC×GC) and tandem mass spectrometry (MS/MS) systems. 6,22,23,[26][27][28] Furthermore, the reduced costs associated, labor intensity and time effectiveness (in spite of long extraction time), are fairly better when compared with other approaches (e.g., SPE, SPME). The developed method is an alternative to current extraction methods, with comparable LOD and LOQ, and satisfactory recovery for trace analysis of α and β-endosulfan in tea and yerba mate samples.…”
Section: Validation Of the Baµe(hlb)/lvi-gc-ms(sim) Methodologymentioning
confidence: 99%
“…Despite a large number of countries and the European Union having already banned the use of endosulfan, 5 residues are still being detected in foods like tea (Camellia sinensis), 6,7 due to its extensive use in China, 3 the world's largest tea grower and exporter. 8 In view of this, different regions have created regulations and set maximum residue levels (MRLs) for endosulfan in tea.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography coupled with mass spectrometry is the most commonly applied and established technique for determination of volatile and semi‐volatile analytes of low medium polarity in water and foods. Different types of MS analyzers have been applied for this goal, such as single‐quadrupole, TOF, ion trap and triple quadrupole; however, the two latter can work under tandem MS mode (Cherta, Beltran, Pitarch, & Hernández, ; Hayward, Wong, & Park, ; Lambropoulou, ; Notardonato, Avino, Cinelli, & Russo, ; Ziarrusta, Olivares, Delgado, Zuloaga, & Etxebarria, ).…”
Section: Gc‐tof‐based Methodsmentioning
confidence: 99%
“…Furthermore, the partition coefficient is lower at high temperature, which results in lower extraction efficacy. [21] Feng et al [9] also reported that VOCs with low molecular weights, including ethanol and ethyl acetate, exhibited lower peak areas at higher temperatures due to lower partition coefficients. On the basis of these experiments, we consider 50°C to be adequate for obtaining the best extraction efficiencies and this temperature was used in subsequent studies.…”
Section: Extraction Temperaturementioning
confidence: 99%